Strategic linking of human resources management and knowledge management practices amongst MSC status companies in Malaysia: enhancing organizational competitiveness - Raja Kasim, Raja Suzana (Universiti Utara Malaysia, 2006)
The purpose of this study is to determine whether the relationships exist between (a) HRM practices; (b) KM practices and (c) organizational competitiveness. In addition, this study also researches whether the use of HRM/KM within the firm leads to the creation of organizational competitiveness between organization that practice HRM/KM and those that do not. A survey is conducted amongst MSC status organizations to determine a common practice of KM and to determine the degree of practices of both HRM/KM. The study determines the relationship between each pair of HRM/KM practices as well organizational competitiveness levels. Organizational competitiveness is assessed by an established measure which integrate the types of innovation and types of performance measures subjectively, namely; comparative performance measure and internal performance measure. HRM/KM practices are assessed from middle level managers both in the area of HRM and non HRM. Result of this research found that there is a positive relationship between HRM/KM practices and organizational competitiveness. Also, results indicate that there are significant differences in the perception of KM/HRM practices among various MSC status organizations, which had KM in place and those that do not.